The Meaning of Military Victory - Mandel, Robert, 1949- (New Delhi Viva Books, 2008)
"How has the concept of victory evolved as the nature of conflict itself has changed across time, circumstance, and culture? And to what end? Robert Mandel Addresses these questions, considering the meanings, misconceptions, and challenges associated with military victory in the context of the nontraditional wars of recent decades."--Jacket.
Includes Notes, Bibliography and Index.
Keywords: War--Termination -- Nation-Building -- World Politics